Fire performance of composites made from carbon/phenolic prepregs with nanoclays. (October 2017) - Asaro, L; Villanueva, S; Alvarez, V; Manfredi, LB; Rodríguez, ES
This article describes the development of fire resistant composite materials based on phenolic resin and carbon fibers. Two types of composites were developed, with neat phenolic resin and with phenolic resin/modified bentonite. Composite materials were processed from prepregs by compression molding and were characterized by density, fiber content, cone calorimeter test, scanning electron microscope, and mechanical properties before and after the exposure to fire. In both cases, high fiber content materials were developed, about 75% by volume. The addition of clay improved some fire properties such as the peak of the heat release rate and the residual mass of the burned samples. Also, the bentonite-modified composite required higher time to develop the maximum of the heat release rate in the material; therefore, the addition of modified nanoclays improved the fire properties of the developed composites. Regarding to mechanical behavior the modified composites presented low modulus and flexural stiffness than the unmodified materials, and presented a higher decreased in the properties after fire, which could be related with the different fiber content in both composites.